2021
DOI: 10.3389/fpsyg.2021.618182
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Experience in Indonesia: Does the Non-smoking Wife Play a Role?

Abstract: ObjectiveMore than 63% of Indonesian men are smokers, and smoking has long been a part of Indonesian culture and the concept of masculinity in Indonesian culture. Given the pro-smoking environment, we were interested in examining why smokers would willingly quit and whether their wives played a role in their quitting process as social factors are mentioned second most frequent as a reason for quitting smoking.DesignIn-depth interviews.MethodWe interviewed 11 couples (N = 22)—ex-smoking husbands and non-smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Considering the methods employed for ending smoking, activating empathy (Shen, 2015 ), explaining the health problems of unborn babies and children (Ayuningtyas et al, 2021a ; Tungtrongvisolkit & Seaharattanapatum, 2021 ), and being supportive (Ayuningtyas et al, 2021a ) were also reported. Persuading their husbands by drawing upon doing good things or being a good model for the baby was supported by the finding that ex-smoker husbands who quit smoking rationalized that they did not want their children to smoke like them (Ayuningtyas et al, 2021b ). Interestingly, our study findings were supported by the previous studies in Thailand in terms of the fear of jeopardizing their marital relationship (Ayuningtyas et al, 2021a ) and relying on their husband’s conscience to quit when no changes in their husband’s smoking behavior (Ayuningtyas et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the methods employed for ending smoking, activating empathy (Shen, 2015 ), explaining the health problems of unborn babies and children (Ayuningtyas et al, 2021a ; Tungtrongvisolkit & Seaharattanapatum, 2021 ), and being supportive (Ayuningtyas et al, 2021a ) were also reported. Persuading their husbands by drawing upon doing good things or being a good model for the baby was supported by the finding that ex-smoker husbands who quit smoking rationalized that they did not want their children to smoke like them (Ayuningtyas et al, 2021b ). Interestingly, our study findings were supported by the previous studies in Thailand in terms of the fear of jeopardizing their marital relationship (Ayuningtyas et al, 2021a ) and relying on their husband’s conscience to quit when no changes in their husband’s smoking behavior (Ayuningtyas et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…For the women who take up smoking this means discontinuing is harder due to not only addiction and peer and other kind of pressures, but a lack of support for overcoming it all [49,50]. having a partner who smokes can influence the spouse's initiation of smoking, or return to smoking after a previous quit attempt [51,52]. In other words, it is possible that a nonsmoking partner can influence his/her spouse to stop smoking [51,53].…”
Section: Pingak Et Al [15]mentioning
confidence: 99%
“…having a partner who smokes can influence the spouse's initiation of smoking, or return to smoking after a previous quit attempt [51,52]. In other words, it is possible that a nonsmoking partner can influence his/her spouse to stop smoking [51,53].…”
Section: Pingak Et Al [15]mentioning
confidence: 99%
See 1 more Smart Citation
“…hipertensi, obesitas, dan merokok. 3,4 Selain itu, kurang dari sepertiga populasi dengan risiko kardiovaskular sedang hingga tinggi tidak menerima pengobatan yang tepat. 5 Studi sebelumnya menemukan bahwa strategi pencegahan primer seperti gaya hidup sehat dan pengendalian dengan obat secara teratur, jarang terjadi pada pria dibandingkan wanita.…”
unclassified